The Syntheses and Crystal Structures of the First Disiloxane‐1, 3‐dithiol and Its Cadmium Complex (Eur. J. Inorg. Chem. 19/2015). Issue 19 (July 2015) - Ciborska, Anna; Conterosito, Eleonora; Milanesio, Marco; Kazimierczuk, Katarzyna; Rzymowska, Katarzyna; Brzozowski, Krzysztof; Dołęga, Anna
Abstract : The cover picture shows the electronic structure and simplified formula of the complicated derivative of orthothiosilicic acid: bis‐1, 3‐[bis(2, 6‐diisopropylphenoxy)]disiloxane‐1, 3‐dithiol. The compound is relatively stable as a result of the kinetic protection of hydrophobic dipp (diisopropylphenyl) substituents and can therefore be utilized as ligand in the synthesis of chelating metal complexes. In the background, one can see large deposits of another silicon compound, namely silicon dioxide (silica, quartz). These deposits, popularly called beaches, are especially wide and beautiful along the Baltic Sea near Gdańsk and were photographed by the corresponding author during a walk with her children on August 5, 2006. Details are discussed in the article by A. Dołęga, E. Conterosito et al. onp. 3059 ff . For more on the story behind the cover research, see theCover Profile .